Inorganic, Organic, and Perovskite Halides with Nanotechnology for High–Light Yield X- and γ-ray Scintillators - Maddalena, Francesco; Tjahjana, Liliana; Xie, Aozhen; Arramel; Zeng, Shuwen; Wang, Hong; Coquet, Philippe; Drozdowski, Winicjusz; Dujardin, Christophe; Dang, Cuong; Birowosuto, Muhammad (Crystals (Basel), 2019)
Trends in scintillators that are used in many applications, such as medical imaging, security, oil-logging, high energy physics and non-destructive inspections are reviewed. First, we address traditional inorganic and organic scintillators with respect of limitation in the scintillation light yields and lifetimes. The combination of high–light yield and fast response can be found in Ce 3 + , Pr 3 + and Nd 3 + lanthanide-doped scintillators while the maximum light yield conversion of 100,000 photons/MeV can be found in Eu 3 + doped SrI 2 . However, the fabrication of those lanthanide-doped scintillators is inefficient and expensive as it requires high-temperature furnaces. A self-grown single crystal using solution processes is already introduced in perovskite photovoltaic technology and it can be the key for low-cost scintillators. A novel class of materials in scintillation includes lead halide perovskites. These materials were explored decades ago due to the large X-ray absorption cross section. However, lately lead halide perovskites have become a focus of interest due to recently reported very high photoluminescence quantum yield and light yield conversion at low temperatures. In principle, 150,000–300,000 photons/MeV light yields can be proportional to the small energy bandgap of these materials, which is below 2 eV. Finally, we discuss the extraction efficiency improvements through the fabrication of the nanostructure in scintillators, which can be implemented in perovskite materials. The recent technology involving quantum dots and nanocrystals may also improve light conversion in perovskite scintillators.